Análise de projetos de infraestrutura com a fronteira de média-variância: o caso dos riscos de atraso e licenciamento ambiental em linhas de transmissão e projetos de geração de energia elétrica no Brasil - Moura, Felipe Fernando de Moraes (2016)
This thesis aims to analyze the supply of infrastructure projects given the current issue on creating long-term financing outside the traditional lines of BNDES; This is an obstacle of the financial sector becomes more relevant even when facing proposals from the federal government to facilitate the concessions. The alternative presented here focuses on diversification of risk and return in the light of the theory of mean-variance portfolio. We will see here that these projects have different profiles of risk-return so that there are potentially significant benefits for the investor to operate diversified portfolio (mix) of projects. The fact exposed here is that traditional valuation approach by leveled costs can not report properly to an operator about the viability of a certain project´s choice given the current portfolio of the firm, with a view that does not take into account the complementarities in risk profiles and return of different projects. Thus, we add the theory of mean-variance portfolio, and the goal is to be able to tell the investor about the project mix allocation (optimal portfolio of assets) using the efficient frontier that minimizes the impact of some critical risks in infrastructure markets. The methodology that will be described later in this paper illustrates a very important problem for the Brazilian electricity sector. The proposed model will be able to incorporate the risks related to delays in construction works and environmental licensing.